2018
DOI: 10.1063/1.5004480
|View full text |Cite
|
Sign up to set email alerts
|

Complex networks for tracking extreme rainfall during typhoons

Abstract: Reconciling the paths of extreme rainfall with those of typhoons remains difficult despite advanced forecasting techniques. We use complex networks defined by a nonlinear synchronization measure termed event synchronization to track extreme rainfall over the Japanese islands. Directed networks objectively record patterns of heavy rain brought by frontal storms and typhoons but mask out contributions of local convective storms. We propose a radial rank method to show that paths of extreme rainfall in the typhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…The authors used a high-resolution (0.25 • × 0.25 • ) monthly gridded precipitation dataset developed by the Indian Meteorological Department (IMD) for the spatial domain of 66.5 to 100 • E and 6.5 to 38.5 • N, covering the mainland region of India (Pai et al, 2014). The gridded data have been generated from the observations of 6995 gauging stations across India (Pai et al, 2014). Details about these data can be obtained from http://imd.gov.in (last access: 13 August 2019) (homepage/rainfall information).…”
Section: Discussionmentioning
confidence: 99%
“…The authors used a high-resolution (0.25 • × 0.25 • ) monthly gridded precipitation dataset developed by the Indian Meteorological Department (IMD) for the spatial domain of 66.5 to 100 • E and 6.5 to 38.5 • N, covering the mainland region of India (Pai et al, 2014). The gridded data have been generated from the observations of 6995 gauging stations across India (Pai et al, 2014). Details about these data can be obtained from http://imd.gov.in (last access: 13 August 2019) (homepage/rainfall information).…”
Section: Discussionmentioning
confidence: 99%
“…Event synchronization (ES) has been specifically designed to calculate nonlinear correlations among bivariate time series with events defined on them (Quiroga et al, 2002). This method has advantages over other time-delayed correlation techniques (e.g., Pearson lag correlation), as it allows us to investigate extreme event series (such as non-Gaussian and event-like datasets) and uses a dynamic time delay (Ozturk et al, 2018). The latter refers to a time delay that is adjusted according to the two time series being compared, which allows for better adaptability to the variable and region of interest.…”
Section: Event Synchronizationmentioning
confidence: 99%
“…As a final note, we emphasize that previous related works (e.g., Ozturk et al, 2018Ozturk et al, , 2019 have employed a different eventbased similarity measure called event synchronization strength (ESS), which is based on a similar rationale as our event coincidence rates (Quiroga et al, 2002). As recent studies have revealed, ESS provides systematically biased values in the presence of temporally clustered events, i.e., events recorded at subsequent time steps, which is not the case for ECA (Hassanibesheli and Donner, 2019;Odenweller and Donner, 2020;Wolf et al, 2020)).…”
Section: Event Coincidence Analysis (Eca)mentioning
confidence: 96%